2021
DOI: 10.3389/fmicb.2021.591535
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Bat-Related Betacoronaviruses: Hazard and Risks

Abstract: The current Coronavirus Disease 2019 (COVID-19) pandemic, with more than 111 million reported cases and 2,500,000 deaths worldwide (mortality rate currently estimated at 2.2%), is a stark reminder that coronaviruses (CoV)-induced diseases remain a major threat to humanity. COVID-19 is only the latest case of betacoronavirus (β-CoV) epidemics/pandemics. In the last 20 years, two deadly CoV epidemics, Severe Acute Respiratory Syndrome (SARS; fatality rate 9.6%) and Middle East Respiratory Syndrome (MERS; fatalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 136 publications
(198 reference statements)
1
60
0
Order By: Relevance
“…Species belonging to the Rhinolophus genus, including R. ferrumequinum , are known natural hosts for numerous SARS-CoV-related betacoronaviruses [9,31]. Alphacoronaviruses [10,32,33], and possibly betacoronaviruses [8], circulate in species belonging to the Myotis genera. Primary cells generated from wing biopsies of R. ferrumequinum , M. myotis , M. nattereri and M. brandtii (table 1) were subjected to infection by SARS-CoV-2 at a multiplicity of infection (MOI) of 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Species belonging to the Rhinolophus genus, including R. ferrumequinum , are known natural hosts for numerous SARS-CoV-related betacoronaviruses [9,31]. Alphacoronaviruses [10,32,33], and possibly betacoronaviruses [8], circulate in species belonging to the Myotis genera. Primary cells generated from wing biopsies of R. ferrumequinum , M. myotis , M. nattereri and M. brandtii (table 1) were subjected to infection by SARS-CoV-2 at a multiplicity of infection (MOI) of 1.…”
Section: Resultsmentioning
confidence: 99%
“…First, comparison of ACE2 protein sequences from 37 bat species, including species of the genus Rhinolophus, predicted a low or very low ability to interact with viral S proteins [20]. Second, expressing ACE2 from dozen bat species in non-permissive mammalian cells possibly betacoronaviruses [8], circulate in species belonging to the Myotis genera. Primary cells generated from wing biopsies of R. ferrumequinum, M. myotis, M. nattereri and M. brandtii (table 1) were subjected to infection by SARS-CoV-2 at a multiplicity of infection (MOI) of 1.…”
Section: Introductionmentioning
confidence: 99%
“…Rulli and co-authors acknowledge that follow-up analyses should consider climate change impacts on bat habitats 10 -entailing more complex feedback with ecosystems 11 , as well as trade-offs and synergies among dietary shifts, food security, wild meat trade and food system shocks 12,13 . Indeed, any zoonotic disease emergence is a complex process also involving societal and economic aspects 14 . In the context of COVID-19, development of therapeutic options, surveillance systems and vaccines are urgent, but strategic actions related to intersectoral collaboration, collective education and awareness raising about the multiple benefits of the One Health approach implementation 15 can mitigate risks associated with anthropized environments 16 .…”
Section: Monia Santinimentioning
confidence: 99%
“…It was recently reported that the Southeast Asian region is a global hotspot of climate change-driven increase in bat-borne coronaviruses [134]. It has also been suggested that there is a need to monitor Southeast Africa and South America for future pandemics, as these regions amalgamate many of the circumstances that could create a perfect storm for new hotspots [135]. For the prevention and treatment of viral pandemics, much can be learned from nature.…”
Section: Has the Therapeutic Dilemma In Covid-19 Already Been Solved In Nature?mentioning
confidence: 99%